2010
DOI: 10.1158/0008-5472.can-09-2968
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Potential of Retinoic Acid Receptor-γ in Hepatocellular Carcinoma

Abstract: Retinoic acid receptors (RAR; α, β, and γ), members of the nuclear receptor superfamily, mediate the pleiotropic effects of the vitamin A metabolite retinoic acid (RA) and derivatives (retinoids) in normal and cancer cells. Abnormal expression and function of RARs are often involved in the growth and development of cancer. However, the underlying molecular mechanisms remain largely elusive. Here, we report that levels of RARγ were significantly elevated in tumor tissues from a majority of human hepatocellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 43 publications
7
59
0
Order By: Relevance
“…Of note, we previously reported that RARg, rather than RARa and RARb, has a unique cytoplasmic localization in many cancer cell types (7). Cytoplasmic accumulation of RARg in HCC cells plays an oncogenic role via nongenomic activation of Akt/NF-kB signaling (10). We here further revealed a surprising nongenomic role of RARg in colorectal cancer, wherein RARg nongenomically regulates the Hippo-Yap pathway via interacting with and sequestering Yap in the cytoplasm.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Of note, we previously reported that RARg, rather than RARa and RARb, has a unique cytoplasmic localization in many cancer cell types (7). Cytoplasmic accumulation of RARg in HCC cells plays an oncogenic role via nongenomic activation of Akt/NF-kB signaling (10). We here further revealed a surprising nongenomic role of RARg in colorectal cancer, wherein RARg nongenomically regulates the Hippo-Yap pathway via interacting with and sequestering Yap in the cytoplasm.…”
Section: Discussionsupporting
confidence: 53%
“…Recent evidence indicated the critical roles of aberrant expression of RARg in tumorigenesis (8,10,13). However, the expression profile and role of RARg in colorectal cancer remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RAR␥ can activate cellular SRC (c-SRC) in the cytoplasm through hormone-dependent direct binding to c-SRC, a process required for neuritogenesis (14). In particular, a recent report revealed that RAR␥ plays an oncogenic role via activation of the Akt/NF-B pathway in the progression of HCC (15). However, the expression profile of RAR␥ protein and its roles and mechanisms in CCA progression remain unknown.…”
mentioning
confidence: 99%